2018
DOI: 10.1159/000496150
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies of Hypertension and Several Other Cardiovascular Diseases

Abstract: Genome-wide association studies (GWAS) have greatly expanded our understanding of the genetic architecture of cardiovascular diseases in the past decade. They have revealed hundreds of suggestive genetic loci that replicate known biological candidate genes and indicate the existence of a previously unsuspected new biology relevant to cardiovascular disorders. These data have been used successfully to create genetic risk scores that may improve risk prediction and the identification of susceptive individuals. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 82 publications
1
44
0
Order By: Relevance
“…It was the rst GWAS study which ushered in the era of gene SNP research on Mets. Since then, the effects of gene polymorphisms have been related to obesity [6], lipid metabolism [7], glucose tolerance and hypertension [8,9]. Because of the heterogeneity and multifactorial nature of Mets, current SNP studies have been limited on single Mets components, the effects of multifunctional gene loci on Mets are seldom reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was the rst GWAS study which ushered in the era of gene SNP research on Mets. Since then, the effects of gene polymorphisms have been related to obesity [6], lipid metabolism [7], glucose tolerance and hypertension [8,9]. Because of the heterogeneity and multifactorial nature of Mets, current SNP studies have been limited on single Mets components, the effects of multifunctional gene loci on Mets are seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the SNP study is still the most important method for Mets gene research. It has been found that over 870 SNPs are associated with obesity [6], 477 SNPs with lipid metabolism [7], more than 200 SNPs with blood pressure [8], and around 250 SNPs with glucose tolerance [9]. However, most of these gene loci were related to single Mets components, among which the lipid metabolism-associated SNPs showed the strongest relevance to Mets [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite large-scale GWASs providing robust evidence for genetic variants in uencing metabolic pathways and CVDs, [18][19][20][21][22][23] it is unclear whether genetic variants exist for CVD within the basis of individual chronic metabolic diseases. The aim of our study was to identify genetic variations associated with CVD among individuals with HTN, DM, and DL, respectively; for which we found varied meaningful loci for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been recently applied to common polygenic diseases, and suggested polygenic risk scores can identify individuals at a similar risk than that conferred by rare monogenic mutations [ 16 ]. Because genetic risk scores can be assessed at birth, they may be particularly useful in risk prediction among younger patients with a reduced cumulative impact of lifestyle factors [ 135 ]. This caveat may explain why genetic risk scores only modestly improve the cardiology-based prognosis for diseases such as AF [ 63 ].…”
Section: Clinical Significance Of Cardiovascular Non-coding Variantsmentioning
confidence: 99%